Quadro reputacional: escolhas eleitorais em uma perspectiva pragmatista - Gomes, Fábio da Silva (2022)
This research investigates the social construction of a reputational reference framework for candidacies for municipal executive positions through a pragmatist approach. The theorical references begin in Charles Senders Peirce’s precursory theories and in George Herbert Mead’s social theory and reach up to, mainly contemporary, pragmatist authors. Thamy Pogrebinschi’s understanding of pragmatism in the identification of the three central ideas in pragmatist theory (anti-foundationalism, consequentialism and contextualism) oriented our point of view and our proposition of the concept of reputation. In Brazil, we highlight Lucia Santaella’s (PUC – SP) interpretations of Peirce’s work and the studies of Grupo de Pesquisa em Imagem e Sociabilidade (GRIS) from UFMG’s Social Communication Department. Starting from our theorical discussions and our research question (reputation and electoral behavior), we debated important propositions which compose the state of the art: Marcus Faria Figueiredo’s examination of electoral behavior in social, psychological and rational fields; Mônica Mata Machado de Castro’s “Political Sofistication Centrality” theory; and Wilson Gomes’ concept of public image. The research hypothesis was elaborated considering three conceptual affirmations: a) reputation is a reference framework which is the result of an intentional action; b) reputation is a socially constructed value which is built in intersubjective interactions; c) The field of reputation is built by sign relations which are presented to perception, and promoted by the relationship between the subject and their everyday environment and social interactions. From these affirmations, we present our hypothesis: voters, in municipal executive election processes elaborate reputational reference frameworks with other voters (as a way of sustaining their thoughts as intentional actions to guide their choices and consequently, their vote decisions) in several interaction processes which consider the expectations and interpretations of the objective world to judge specific candidacies’ reputations. In order to try to prove our hypothesis, we defined our field research’s corpus as the data which was collected in cities from Rio de Janeiro State according to regions and electoral size. Qualitative methodology was applied in the form of in-depth interviews in two Fluminense cities: Rio de Janeiro and Paty do Alferes. Through this methodology, we looked for discursive patterns related to the following evaluation points: lived world characteristics (objective world), interpretations regarding social context (perceived world), references to judge candidacies (reputational framework) and electoral campaign’s language (promised world). With this, we intend to answer the following research question: is the vote preceded by the social construction of referential frameworks, used for judgments and candidacies choices?